Efektivitas Pelatihan Komunikasi Interpersonal Untuk Meningkatkan Kerjasama Antar Remaja PM3 Dusun Mertoyudan Kabupaten Magelang - Ilham, Muhammad; Indiati, Indiati; Putro, Hijrah Eko (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effectiveness of interpersonal communication training to improve cooperation between adolescents. This research uses One Group Pretest-Poesttest Design. The samples taken in this study were 8 teenagers consisting of one experimental group. Sampling using random sampling technique. Methods of data collection is done by using a cooperative questionnaire. The data analysis method used is parametric analysis Paired sample t-test. The results of this study indicate that interpersonal communication training can have an effect on increasing cooperation between adolescents. This is evidenced by the Paired Sample T Test with a significance probability value (2-tailed) 0.000 <0.05. Based on the results of the study, there was a difference in the average score of the 20% Cooperation questionnaire from the results of the pretest and posttest. The results of the study can be concluded that interpersonal communication training is able to increase cooperation between adolescents.